Aplicación de la teoría “Lean Construction” en actividades representativas de mantenimiento rutinario en carreteras asfaltadas - Macedo Del Águila, César Anderson (2009)
This thesis has as objective apply them concepts basic of the philosophy Lean Construction in the management of the maintenance routine and of emergency and its se as tool practice in the identification of losses. As well as also stablecerindicadores for the improvement of the performance of the projects ransported this study. This became a theoretical explanation of what is Lean Construction and basic concepts of maintenance activities, were evaluated only cleaning of spills of fuel, transport of materials, covered ditches cleaning and uncoated, weed removal, mulching of weed with computer, folder, patch asphalt patching in berms, cleaning replacement of concrete curbs , cleaning and minor landslides, formation of talus, cleaning of ditches with equipment, construction of emboquillados's stone, treatment of cracks and fissures of the pavement with slurry seal, replacement and repair of guardian...